Nobiletin ameliorates glucose tolerance by protecting against β-cell loss in type-2 diabetic db/db mice - Yukiko K. Kaneko; Yuki Tara; Stella Amarachi Ihim; Moe Yamamoto; Megumi Kaji; Tomohisa Ishikawa (Elsevier, 2022)
Background: Nobiletin, a polymethoxy flavone contained in the peel of Citrus reticulata, has been known to have health benefits especially those related to improvement of type 2 diabetes. Our previous in vitro study demonstrated the insulinotropic and anti-apoptotic effects of nobiletin in pancreatic β-cells. These effects of nobiletin are postulated to be responsible for its anti-diabetic activity. Purpose: We evaluated the anti-diabetic effects of nobiletin on pancreatic β-cells of type 2 diabetic db/db mice. Methods: Nobiletin was filled into an osmotic pump and implanted subcutaneously in the back of db/db mice for 2 weeks with continuous administration. The mice were then used for the experiments to elucidate the in vivo effects of nobiletin on glucose intolerance. Results: The continuous subcutaneous administration of nobiletin using osmotic pumps significantly reduced blood glucose levels in non-fasting state and during an oral glucose tolerance test. The nobiletin administration also ameliorated insulin sensitivity determined by insulin tolerance test, which was likely due to a reduction of white adipose tissue weight. In addition, β-cell mass was significantly larger in nobiletin-administered db/db mice compared to vehicle-administered db/db mice. These results suggest that continuous administration of nobiletin ameliorates glucose tolerance in type 2 diabetes, which is mediated by improving not only insulin resistance but also insulin secretion, the latter being due to protection against β-cell loss in diabetes. Conclusion: Nobiletin would have a valuable effect on the prevention of type 2 diabetes.